Janus kinase and signal transducer and activator of transcription inhibitors in type 1 diabetes and immune checkpoint–related diabetes: current status and future perspectives - Su, Bowei; Luan, Zhi-Lin; Liu, Haixia; Tuomilehto, Jaakko; Ji, Xiaochen (Frontiers in Immunology, 2025)
Type 1 diabetes (T1D) is an autoimmune-mediated disorder that leads to the destruction of pancreatic beta-cells, insulin deficiency, and chronic hyperglycemia. It is one of the most common childhood endocrine disorders. Recent evidence indicates that aberrant Janus kinase–signal transducer and activator of transcription (JAK/STAT) signaling exacerbates T1D by promoting the production of proinflammatory cytokines and chemokines. By blocking JAK-mediated phosphorylation of STAT proteins, JAK inhibitors help alleviate cytokine-driven inflammation, reduce insulin requirements, and relieve complications such as painful peripheral neuropathy, potentially preserving residual beta-cell function and improving glycemic control. Moreover, emerging data underscore the potential synergy between JAK inhibitors and immune checkpoint therapies targeting the programmed cell death protein 1 (PD-1) pathway, as PD-1/Programmed cell death ligand 1 (PD-L1) inhibitors used in antitumor therapy can induce immune checkpoint inhibitor–induced diabetes (CPI-DM). This review examines the impact of JAK inhibitors on beta-cells and immune cells in T1D, along with their safety profiles and adverse effects. It explores the potential benefits and risks of combining JAK inhibitors in the management of CPI-DM associated with anti–PD-1/PD-L1 therapy. In conclusion, while JAK inhibitors have demonstrated the potential to reduce inflammation and preserve beta-cell function in preclinical studies, further clinical trials are needed to confirm their long-term safety and efficacy in patients with T1D and CPI-DM.